Rubber arm with fluid system for venipuncture training, new model in clinical skills tutors - Jarintanan, Faongchat; Chanprasert, Kanchana; kongwan, Weerachai; Ratanawiboolsook, Nalinpas; Pawinwongcha, Jaturawat; Liemmanee, Weerawat (Progress in Applied Science and Technology, 2016)
The newly developed artificial arm allows puncture practice with an arm model that has similar touch to human arms, providing effective training environment for blood drawing. The rubber arm (RA) with a fluid system for venipuncture which duplicates the 3 veins of the human arm as closely as innovative technology allows. The venous system simplifies setup with only one internal fluid box and pump supplying artificial blood to all veins simultaneously. The antecubital fossa includes the median cephalic, median basilic, and median cubital veins in the rubber arm. The Rubber arm with fluid system was developed by integrating five-degrees. Subjective responses such as perception of the RA and perceived fall were measured by questionnaires. Experiment 1 shows strong agreement and agreement in virtual arm (94%) sized (93%) and color (63%). In experiment 2, 99.9 % were able to perfect the technique of venipuncture; to draw blood from veins. This research investigated the possibility of the rubber arm fluid system using matched or mismatched medical science students of venipuncture training . It can help with confidence and understanding the steps in the first draw after using this model.